Reconstructing climate patterns in Europe during the LGM from inversions of past ice extents - Vjeran Višnjevic (Zenodo, 2019)
Over 20 ky ago, Earth experienced its last large scale glacial advance. Ice sheets and ice caps covered large areas in both the Northern and the Southern Hemisphere. Conditions over Europe were cold and dry, with both the Scandinavian Peninsula and the British Isles in the north, as well as the Alps and the Pyrenees in central and western Europe, covered by ice. The influence of these ice sheets and ice caps on the atmospheric circulation, and to what point did the ice sheets in the north, and the subsequent expansion of the polar front, control the position of the Westerly winds and the regional precipitation patterns over Europe, remains a topic of debate. Secondly, there is a strong need for additional constraints on the amplitudes of mean temperature and precipitation changes compared to present-day. Although there is a discrepancy between observations and the modeling studies on both issues, it is clear that proper representation of ice surface topography in the models will strongly effect on the outcomes of such paleoclimate reconstructions. The approach presented in this study will be to combine ice flow modeling with the geomorphological evidence these ice caps and ice sheets left in the landscape in the form of moraines and trimlines. This approach enables us to gain insights into past climate conditions, by constraining changes and exploring patterns in temperature and precipitation across a mountain range, thus recovering valuable information on the regional atmospheric circulation over Europe. In order to investigate these questions, I have developed an inverse method to reconstruct the spatially variable mass balance rate of an ice cap, and in return the spatially variable position of the Equilibrium line altitude (ELA), using mapped ice extent and ice thickness data as input. The method is applied to the mountain ranges of the Alps and the Pyrenees, as they are effected by the same regional climate, and the recovered spatial variability in the patterns of the ELA reflects patterns in temperature ...